Effectiveness of pulic screening for glaucoma in republic of Kazakhstan - Tashtitova, L.B.; Botabekova, Т.К.; Aldasheva, N.A.; Uteuliyev, E.S. (My University, 2016)
In the Republic of Kazakhstan (RK) glaucoma is the second place ranking in the structure of primary disability on eyesight. In 80.2% of cases-these are invalids of the first or second group (Islamova S.E., 2009). In 2010 there was signed a decree of the President of the RK «On approval of the State Program for Health Development in RK «Salamatty Kazakhstan/ Healthy Kazakhstan)) for 2011-2015». According to decree glaucoma entered in the category of socially significant diseases subject to screening detection
Keywords: screening for glaucoma; the detection of glaucoma